Komunitas Makrozoobentos dan Akumulasi Kromium di Sungai Cimanuk Lama, Jawa Barat - Arbi Mei Gitarama; Majariana Krisanti; Dewi Ratih Agungpriyono (Institut Pertanian Bogor, 2016)
The residue of human activities and batik industrial waste water surrounding the river will be able to increase the accumulation of chromium and to disrupt macrozoobenthic communities in the river. The aims of this study was to assess the impact of human activities surrounding the river to the macrozoobenthic communities and the accumulation of chromium in Cimanuk Lama River, Indramayu District, West Java. The study has been conducted from AprilMay 2015 based on three times sampling at three different sampling stations. The result of this study shows that the chromium accumulated in the waters of all station still meet the standard quality ranging from 0,010-0,016 mg/l, but only station 1 fulfills the standard quality for chromium accumulated in the river sediment with the range of all stations was about 11,72-46,63 mg/kg. The results also show that the community index analysis describes the change of macrozoobenthic community at all stations caused by environmental pressure, especially at the station 2 which is indicated by the highest score of Family Biotic Index. The accumulation of the chromium in the waters and the change of macrozoobenthic community structure are mostly influenced by the use of the Cimanuk Lama river long for agricultural and fisheries activities, and also batik home industry.